THE USE OF BRITISH BROADCASTING CORPORATION (BBC) PODCAST IN EFL STUDENTS' LISTENING SKILL IN IAIN PALANGKA RAYA - Rachmiati, Desy; Qalyubi, Imam; Qamariah, Zaitun (PROJECT (Professional Journal of English Education), 2021)
A podcast is a digital multimedia file that can be downloaded to a portable media player, phone, or other device via the internet. There are many audio podcast that can be used in learning listening, one of them is British Broadcasting Corporation (BBC) podcast. This research aimed to describe how the contribution and the problems in using British Broadcasting Corporation (BBC) podcast in EFL students’ listening skill. This research was conducted at IAIN Palangka Raya. The type of this study was a qualitative approach. The data was taken from interview and documentation. Eight EFL students and two lecturers in IAIN Palangka Raya were the subjects of this research. They were determined by purposive sampling technique. The findings reveal that the use of British Broadcasting Corporation (BBC) podcast give positive contribution to students’ listening skill. Based on the result of the research using British Broadcasting Corporation (BBC) podcast can develop students’ listening skill, vocabularies and they will be familiar with British accent. The problems in using the BBC podcast faced by the students were unfamiliar pronunciation, lack of vocabularies, and the speaker who spoke fast. Keywords:  Podcast, British Broadcasting Corporation (BBC) podcast, EFL students, listening skill